Macrophage Phenotype and Function in Liver Disorder - Dou, Lang; Shi, Xiaomin; He, Xiaoshun; Gao, Yifang (Frontiers in Immunology, 2020)
Hepatic macrophages are a remarkably heterogeneous population consisting of self-renewing tissue-resident phagocytes, termed Kupffer cells (KCs), and recruited macrophages derived from peritoneal cavity as well as the bone marrow. KCs are located in the liver sinusoid where they scavenge the microbe from the portal vein to maintain liver homeostasis. Liver injury may trigger hepatic recruitment of peritoneal macrophages and monocyte-derived macrophages. Studies describing macrophage accumulation have shown that hepatic macrophages are involved in the initiation and progression of various liver diseases. They act as tolerogenic antigen-presenting cells to inhibit T-cell activation by producing distinct sets of cytokines, chemokines, and mediators to maintain or resolve inflammation. Furthermore, by releasing regenerative growth factors, matrix metalloproteinase arginase, they promote tissue repair. Recent experiments found that KCs and recruited macrophages may play different roles in the development of liver disease. Given that hepatic macrophages are considerably plastic populations, their phenotypes and functions are likely switching along disease progression. In this review, we summarize current knowledge about the role of tissue-resident macrophages and recruited macrophages in pathogenesis of alcoholic liver disease (ALD), non-alcoholic steatohepatitis (NASH), viral hepatitis, and hepatocellular carcinoma (HCC).